Diffuse glioblastoma resembling acute hemorrhagic leukoencephalitis - Schettino, Carla; Caranci, Ferdinando; Lus, Giacomo; Signoriello, Elisabetta; Eoli, Marica; Anghileri, Elena; Pollo, Bianca; Melone, Mariarosa A. B.; Iorio, Giuseppe Di; Finocchiaro, Gaetano; Ugga, Lorenzo; Tedeschi, Enrico (Quantitative Imaging in Medicine and Surgery; Vol 7, No 5 (October 31, 2017): Quantitative Imaging in Medicine and Surgery, 2017)
We report the case of a young man with sudden onset of diplopia after an upper respiratory tract infection. Based on the first radiological findings acute hemorrhagic leukoencephalitis, a variant of acute disseminated encephalomyelitis, was suspected and treatment with high dose intravenous dexamethasone was started but it was stopped for intolerance. The patient clinically worsened, developing gait instability, ataxia and ophthalmoplegia; brain MRI performed 20 days later showed severe progression of the disease with subependymal dissemination. After brain biopsy of the right temporal lesion the histological diagnosis was glioblastoma. These findings suggest that MRI features of acute hemorrhagic leukoencephalitis may dissimulate the diagnosis of diffuse glioma/glioblastoma. This case underscores the importance of considering diffuse glioma in the differential diagnosis of atypical signs and symptoms of acute hemorrhagic leukoencephalitis and underlines the relevant role of integrating neuroradiologic findings with neuropathology.